Diet-induced weight loss alters hepatic glucocorticoid metabolism in type 2 diabetes mellitus. Issue 4 (April 2020) - Stomby, Andreas; Otten, Julia; Ryberg, Mats; Andrew, Ruth; Walker, Brian R; Olsson, Tommy
Abstract : Context: Altered tissue-specific glucocorticoid metabolism has been described in uncomplicated obesity and type 2 diabetes. We hypothesized that weight loss induced by diet and exercise, which has previously been shown to reverse abnormal cortisol metabolism in uncomplicated obesity, also normalizes cortisol metabolism in patients with type 2 diabetes. Objective: Test the effects of a diet intervention with added exercise on glucocorticoid metabolism. Design: Two groups followed a Paleolithic diet (PD) for 12 weeks with added 180 min of structured aerobic and resistance exercise per week in one randomized group (PDEX). Setting: Umeå University Hospital. Participants: Men and women with type 2 diabetes treated with lifestyle modification ± metformin were included. Twenty-eight participants (PD, n = 15; PDEX, n = 13) completed measurements of glucocorticoid metabolism. Main outcome measures: Changes in glucocorticoid metabolite levels in 24-h urine samples, expression of HSD11B1 mRNA in s.c. adipose tissue and conversion of orally administered cortisone to cortisol measured in plasma. Body composition and insulin sensitivity were measured using a hyperinsulinemic-euglycemic clamp, and liver fat was measured by magnetic resonance spectroscopy. Results: Both groups lost weight and improved insulin sensitivity. Conversion of orally taken cortisone to plasma cortisol and the ratio of 5α-THF + 5β-THF/THE in urine increased in both groups. Conclusions: These interventions caused weight loss and improved insulin sensitivity with concomitant increases in the conversion of cortisone to cortisol, which is an estimate of hepatic HSD11B1 activity. This suggests that dysregulation of liver glucocorticoid metabolism in these patients is a consequence rather than a cause of metabolic dysfunction.